2018
DOI: 10.1177/0892705718799823
|View full text |Cite
|
Sign up to set email alerts
|

Water absorption behavior of heat-treated and untreated red balau saw dust/LDPE composites: Its kinetics and effects on mechanical properties

Abstract: The hygroscopic nature of wood limits the use of wood thermoplastic composites (WTC) in outdoor industrial and domestic applications. To reduce this tendency, red balau saw dust was heat treated at 180 and 200°C for 1 h and compounded with Low Density Poly(ethylene) (LDPE) into 20 and 37 wt% and then molded into test specimens by injection molding. Samples were immersed in distilled water at room temperature for 4 months. Heat-treated wood composites showed remarkable water resistance relative to untreated one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Therefore, in high humidity, water sensitivity will increase leading to higher moisture absorption. 79…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in high humidity, water sensitivity will increase leading to higher moisture absorption. 79…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in high humidity, water sensitivity will increase leading to higher moisture absorption. 79 Figure 6((a) and (b)) shows that moisture absorption of MOSF-PVA composite immersed in distilled water is higher than in saline water. This is because of salt molecules which lower the action of water molecules and results in accession of salts particles on the surface of sheet which could further obstruct the water uptake.…”
Section: Moisture Absorption Test Of Mosf-pva Filmmentioning
confidence: 98%
“…The solutions for the improved moisture resistant properties are a correct coupling agent [7,10], or an additive such as silane treatment that decreases water uptake with increasing concentration [12]. Filler modification, such as heat treatment, can also reduce water absorption due to its reduced hydrophilicity [13]. The swelling of materials has a connection with water absorption, but the polymer also has an influence on the moisture behavior.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Jana and Prieto 25 reported that although the addition of coupling agents on WPCs lowers the rate at which of moisture diffuses into composite, adverse effects are noticed on their tensile and impact strength. Furthermore, Lafia-Araga et al 26 discovered that heat-treated wood composites exhibited lower tendency to water absorption as a result of the reduced hydrophilicity imparted to the wood by heat modification.…”
Section: Introductionmentioning
confidence: 99%